Green Banking: An Approach Towards Environmental Management - Tara, Kanak; Singh, Saumya (Prabandhan: Indian Journal of Management, 2015)
The world has witnessed much focus on economic progress but has also neglected environmental issues. This negligence today has led to huge losses in terms of climate change, biodiversity, environmental degradation, rising green house gases, loss of forests and water resources, and so forth. This degrading situation of the environment has led to a call by the society for taking responsibility to safeguard the planet . The corporates, thus have shifted their focus from the single bottom line, that is, profit to the wider approach of "triple bottom line" in lieu of achieving economic, social, and environmental performance simultaneously for attaining sustainable development. Today, every sector of the world economy is talking about their approach towards protection of the environment, and the financial sector moving towards their ’going green’ approach in no exception. Various financial services which have adopted green approach in their businesses are banks, stock brokerages, insurance companies, and consumer finance companies. This paper aimed at finding out the various initiatives taken by the Indian banking industry to protect the natural environment and bring about sustainable development in the society.